Therapeutic and prophylactic effect on periodontal on the background of refusal of smoking - M. V. Osipova; L. Yu. Orekhova; E. A. Belova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The article discusses a new method for estimating the saturation of a therapeutic and prophylactic effect on periodontal on the background of refusal of smoking and its application to assess the parameters of periodontal transitions from the stage of exacerbation to the stage of remission.The objective was to improve the accuracy of low-cost prediction of the effectiveness of interventions in inflammatory periodontal diseases in smoking patients based on the development of a new method for assessing the saturation of therapeutic and prophylactic effects.Methods and materials. To determine the saturation of therapeutic and prophylactic effects on periodontal in smoking patients, it was proposed to estimate the weighted average increase in the reduction of a new series of indicators (concentration of carbon monoxide in exhaled air, clinical indices and frequency of occurrence and nature of exudate of periodontal spaces).Results. The saturation of the therapeutic and prophylactic effect on periodontal on the background of quitting (using anti-tobacco patches) when conducting events with xanthan gel with chlorhexidine or photo-activated disinfection occurs much earlier than the two-week interval. Estimates of the relative frequencies and intensities of therapeutic and prophylactic transitions are obtained when performing procedures against the background of nicotine replacement therapy.Conclusion. The proposed method for assessing the saturation of the therapeutic and prophylactic effect on periodontal in smoking patients allows to take into account additional features of the analyzed process and to carry out a low-cost prediction of the effectiveness of complex therapy.Authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.